Assessment of the Farmer Field Schools Activities as Strategy to Enhance Capacity Building of Smallholder Rural Cocoa Farmers in Kwara State, Nigeria - Fatai, K.; Abdullahi, H. A.; Oba, A. I.; Bijani, Masoud (Indonesian Journal of Agricultural Research, 2024)
The study assessed the Farmer Field Schools (FFS) activities as a strategy to enhance capacity building of rural smallholder cocoa farmers in Kwara State, Nigeria. A descriptive survey to enhance the capacity to conduct the research. A purposive sampling procedure was used to select 160 smallholder rural cocoa farmers who participated in the FFS activities in Kwara State. A structured interview schedule was used to collect the data from the respondents. Data were gathered on the socio-economic characteristics of smallholder cocoa farmers and the skills provided by FFS to smallholder cocoa farmers. Data was analyzed using mean, frequency counts, percentages, and chi-square at 0.05 level of significance. The result revealed that 91.3% were male, while 8.7% were female. The result showed that all the skills needed were provided by FFS. The results showed that FFS activities had a significant relationship with the FFS skills provided and the training needs of the rural smallholder cocoa farmers with a p-value of 0.001 being < 0.05. The findings concluded that farmer field school activities had a positive relationship between the skills provided and the training needs of cocoa farmers and this is because the skills provided by FFS are in line with the training needs of cocoa farmers. The study recommends that the Kwara State Ministry of Agriculture through the FFS should continue to serve as a training base that involves more farmers in the program and encourage extension service delivery to encourage capacity building and increase productivity.